Distinct roles for different Homer1 isoforms in behaviors and associated prefrontal cortex function - Lominac, Kevin Daniel; Klugmann, Matthias (The journal of neuroscience, 2005)
Homer1 mutant mice exhibit behavioral and neurochemical abnormalities that are consistent with an animal model of schizophrenia. Because the Homer1 gene encodes both immediate early gene (IEG) and constitutively expressed (CC) gene products, we used the local infusion of adeno-associated viral vectors carrying different Homer1 transcriptional variants into the prefrontal cortex (PFC) to distinguish between the roles for IEG and CC Homer1 isoforms in the “schizophrenia-like” phenotype of Homer1 mutant mice. PFC overexpression of the IEG Homer1 isoform Homer1a reversed the genotypic differences in behavioral adaptation to repeated stress, whereas overexpression of the constitutively expressed Homer1 isoform Homer1c reversed the genotypic differences in sensorimotor and cognitive processing, as well as cocaine behavioral sensitivity. Homer1a overexpression did not influence PFC basal glutamate content but blunted the glutamate response to cocaine in wild-type mice. In contrast, Homer1c overexpression reversed the genotypic difference in PFC basal glutamate content and enhanced cocaine-induced elevations in glutamate. These data demonstrate active and distinct roles for Homer1a and Homer1c isoforms in the PFC in the mediation of behavior, in the maintenance of basal extracellular glutamate, and in the regulation of PFC glutamate release relevant to schizophrenia and stimulant abuse comorbidity.